Epigenetics and Cancer. - Herceg, Zdenko; Ushijima, Toshikazu (Advances in genetics ;, 2010)
Genes interact with environment, experience, and the biology of the brain to shape an animal's behavior. This latest volume in Advances in Genetics, organized according to the most widely used model organisms, describes the latest genetic discoveries in relation to neural circuit development and activity. * Explores latest topics in neural circuits and behavior research in zebrafish, drosophila, c.elegans, and mouse models * Includes methods for testing with ethical, legal, and social implications * Critically analyzes prospects future prospects.